Method of EAS's Cherenkov and fluorescent light separation using silicon photomultipliers. (February 2019) - Chernov, Dmitry; Bonvech, Elena; Dzhatdoev, Timur; Finger, Miroslav; Finger, Michael; Galkin, Vladimir; Garipov, Gali; Kozhin, Vladimir; Podgrudkov, Dmitry; Skurikhin, Alexander
Abstract: Preliminary results on the development of a separation method for Cerenkov (CL) and fluorescence (FL) light from EAS are shown. The results are based on the measurement of attenuation coefficients of CL and FL for different filters. A total of six optical filters were investigated: filters from optical glass UFS-1, UFS-5, FS6 (analogue BG3) and interference filters SL 360-50, SL 280-380, FF01-375/110. The measurements were performed using silicon photomultipliers (SiPM). To improve existing fluorescent light detectors, a segment of 7 SiPM was developed, which would be able to separate both components of the light flux from EAS at the level of primary data processing.